2009
DOI: 10.1111/j.1574-6976.2008.00141.x
|View full text |Cite
|
Sign up to set email alerts
|

Computational and experimental approaches to chart theEscherichia colicell-envelope-associated proteome and interactome

Abstract: The bacterial cell-envelope consists of a complex arrangement of lipids, proteins and carbohydrates that serves as the interface between a microorganism and its environment or, with pathogens, a human host. Escherichia coli has long been investigated as a leading model system to elucidate the fundamental mechanisms underlying microbial cell-envelope biology. This includes extensive descriptions of the molecular identities, biochemical activities and evolutionary trajectories of integral transmembrane proteins,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 189 publications
(363 reference statements)
3
50
0
Order By: Relevance
“…Six of the seven orphans of this particular neighborhood are predicted to localize to the E. coli inner membrane [38]. We found that deletion of these orphans results in hypersensitivity to an otherwise exported drug, similar to that observed upon loss of the annotated components (Figure 7E), suggesting equal participation in the maintenance of cell homeostasis.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…Six of the seven orphans of this particular neighborhood are predicted to localize to the E. coli inner membrane [38]. We found that deletion of these orphans results in hypersensitivity to an otherwise exported drug, similar to that observed upon loss of the annotated components (Figure 7E), suggesting equal participation in the maintenance of cell homeostasis.…”
Section: Resultssupporting
confidence: 69%
“…For the negative gold standards, we compiled pairs of proteins annotated with different subcellular localizations (i.e., one cytoplasmic, the other periplasmic or outer membrane-bound [38]. …”
Section: Resultsmentioning
confidence: 99%
“…The study identified 263 novel proteins potentially associated with the Symbiosis Interactome, and the topology of the Symbiosis Interactome was used to guide experimental techniques attempting to validate novel proteins involved in different stages of symbiosis. The second approach is proteomic analysis of the protein complexes, typically performed using affinity tag/pull-down of large protein complexes and then MS/MS characterization at a proteome level (Butland et al, 2005;Gingras et al, 2005;Krogan et al, 2006;Díaz-Mejía et al, 2009). Using this approach, some subsets of the interactomes, such as cell-envelopeassociated proteome and interactome in Escherichia coli, have been studied .…”
Section: Interactomicsmentioning
confidence: 99%
“…Knowledge of cell envelope protein–protein interactions (cePPIs) and their physical and functional organization into multiprotein complexes (MPCs) therefore provides critical information into the basic systems governing prokaryotic physiology, which in turn is essential to combat infections by antibiotic-resistant pathogens. Yet while previous small-scale investigations in E. coli have identified certain MPCs required for peptidoglycan synthesis, chemotaxis, lipopolysaccharide (LPS) export and envelope assembly 2,4,5 , experimental data concerning the binding partners and functions of most bacterial CEPs are still lacking 6 .…”
mentioning
confidence: 99%